Accelerated multi‐snapshot free‐breathing B1+ mapping based on the dual refocusing echo acquisition mode technique (DREAM): An alternative to measure RF nonuniformity for cardiac MRI. Issue 2 (15th November 2018) - Rincón‐Domínguez, Teresa; Menini, Anne; Solana, Ana Beatriz; Fischer, André; Kudielka, Guido; Haase, Axel; Burschka, Darius
Abstract : Background: Field inhomogeneities in MRI caused by interactions between the radiofrequency field and the patient anatomy can lead to artifacts and contrast variations, consequently degrading the overall image quality and thereby compromising diagnostic value of the images. Purpose: To develop an efficient free‐breathing and motion‐robust B 1 + mapping method that allows for the investigation of spatial homogeneity of the transmitted radiofrequency field in the myocardium at 3.0T. Three joint approaches are used to adapt the dual refocusing echo acquisition mode (DREAM) sequence for cardiac applications: (1) electrocardiograph triggering; (2) a multi‐snapshot undersampling scheme, which relies on the Golden Ratio, to accelerate the acquisition; and (3) motion‐compensation based on low‐resolution images acquired in each snapshot. Study type: Prospective. Phantom/subjects: Eurospin II T05 system, torso phantom, and five healthy volunteers. Field strength/sequence: 3.0T/DREAM. Assessment: The proposed method was compared with the Bloch‐Siegert shift (BSS) method and validated against the standard DREAM sequence. Cardiac B 1 + maps were obtained in free‐breathing and breath‐hold as a proof of concept of the in vivo performance of the proposed method. Statistical tests: Mean and standard deviation (SD) values were analyzed for six standard regions of interest within the myocardium. Repeatability was assessed in terms of SD and coefficient of variation. Results: Phantom results indicated low deviation from the BSS method (mean difference = 3%). Equivalent B 1 + distributions for free‐breathing and breath‐hold in vivo experiments demonstrated the motion robustness of this method with good repeatability (SD < 0.05). The amount of B 1 + variations was found to be 26% over the myocardium within a short axis slice. Data conclusion: The feasibility of a cardiac B 1 + mapping method with high spatial resolution in a reduced scan time per trigger was demonstrated. The free‐breathing characteristic could be beneficial to determine shim components for multi‐channel systems, currently limited to two for a single breath‐hold. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:499–507.